Seizure is a rare presentation for acute hemolysis due to G6PD deficiency. We report a previously healthy boy who presented initially with seizure and cyanosis and subsequently acute hemolysis, due to glucose-6-phosphate dehydrogenase deficiency (G6PD) an - FAYYAZI, Afshin; KHAJEH, Ali; ESFAHANI, Hosein (Iranian Journal of Child Neurology, 2012)
Seizure is a rare presentation for acute hemolysis due to G6PD deficiency. We report a previously healthy boy who presented initially with seizure and cyanosis and subsequently acute hemolysis, due to glucose-6-phosphate dehydrogenase deficiency (G6PD) and probably secondary methemoglobinemia, following the ingestion of fava beans.